Awakening Revealed through Rose's Visual Analysis on #LangkahHijau Commercial Ads - Andreas Lumampauw; Rini Lestari; Rustono Farady Marta; Joshua Fernando (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2020)
Fundraising through digital technology, also known as crowdfunding is an easier, faster and more accurate alternative to donating for modern society. People who use mobile technology are able to always be connected to the internet to carry out various online activities from anywhere, including for fundraising activities. Apart from helping fellow human beings, donating activities can also be carried out as a form of program or activity to care for the environment and to improve the quality of air, land and water. One of them is a crowdfunding activity which is a form of concern from Grab Indonesia to improve air quality by inviting the public and users of Grab services to reduce their carbon footprint through the Carbon Offsetting campaign facilitated by WRI Indonesia and BenihBaik.com. One of the communication media used is the video advertisement “Kurangi Jejak Karbon #LangkahHijau Dengan Menanam Pohon - BenihBaik.com x Grab Indonesia x WRI” on YouTube social media. This article is compiled with a constructivist paradigm with the aim of carrying out a systematic analysis of the meaning contained in video advertisements through the Visual Analysis method by Gillian Rose supported by ten advertising analysis instruments and is based on Erwin Panofsky's Iconography theory. The results of this study indicate that there is a sense of awakening that people's daily lives have the power to destroy the Earth and the environment, but at the same time there are efforts to heal the Earth back into beauty. Key words: awakening, carbon footprint, crowdfunding, hashtag langkah hijau, visual analysis